Calibration of the SHERLOC Deep Ultraviolet Fluorescence–Raman Spectrometer on the Perseverance Rover. Issue 7 (July 2021) - Uckert, Kyle; Bhartia, Rohit; Beegle, Luther W.; Monacelli, Brian; Asher, Sanford A.; Burton, Aaron S.; Bykov, Sergei V.; Davis, Kristine; Fries, Marc D.; Jakubek, Ryan S.; Hollis, Joseph Razzell; Roppel, Ryan D.; et al.
We describe the wavelength calibration of the spectrometer for the scanning of habitable environments with Raman and luminescence for organics and chemicals (SHERLOC) instrument onboard NASA's Perseverance Rover. SHERLOC utilizes deep ultraviolet Raman and fluorescence (DUV R/F) spectroscopy to enable analysis of samples from the Martian surface. SHERLOC employs a 248.6 nm deep ultraviolet laser to generate Raman-scattered photons and native fluorescence emission photons from near-surface material to detect and classify chemical and mineralogical compositions. The collected photons are focused on a charge-coupled device and the data are returned to Earth for analysis. The compact DUV R/F spectrometer has a spectral range from 249.9 nm to 353.6 nm (∼200 cm −1 to 12 000 cm −1 ) (with a spectral resolution of 0.296 nm (∼40 cm −1 )). The compact spectrometer uses a custom design to project a high-resolution Raman spectrum and a low-resolution fluorescence spectrum on a single charge-coupled device. The natural spectral separation enabled by deep ultraviolet excitation enables wavelength separation of the Raman/fluorescence spectra. The SHERLOC spectrometer was designed to optimize the resolution of the Raman spectral region and the wavelength range of the fluorescence region. The resulting illumination on the charge-coupled device is curved, requiring a segmented, nonlinear wavelength calibration in order to understand the mineralogy and chemistry of Martian materials. Graphical Abstract